2018
DOI: 10.1136/bcr-2017-223848
|View full text |Cite
|
Sign up to set email alerts
|

Total midgut duplication: a ticking time bomb

Abstract: A day-old neonate presented with bowel obstruction and an abdominal mass. Exploratory laparotomy revealed complete tubular midgut duplication from duodeno-jejunal junction up to terminal ileum which was communicating with the ileum distally. At the proximal end, another 5×5 cm duplication cyst was identified and excised. Postoperatively, complaints were relieved. During follow-up, 99m-Tc-pertechnetate-SPECT scan showed ectopic gastric mucosa in lower abdomen and in the right hemithorax. CECT-chest showed a 3×3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Preoperative presentation is usually GI bleed,[ 5 6 7 ] features of sepsis,[ 6 ] or abdominal pain. [ 3 ] The abdominal lump has been detected in cases with associated cystic duplications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative presentation is usually GI bleed,[ 5 6 7 ] features of sepsis,[ 6 ] or abdominal pain. [ 3 ] The abdominal lump has been detected in cases with associated cystic duplications.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative radiological findings have usually identified associated cystic duplication. [ 3 5 ] Occasionally, long tubular duplication has been picked up by preoperative sonography as a large well-defined cystic lesion with thick walls with gut signature and internal debris[ 6 ] – the patient in this report was sick with features of GI bleed and sepsis – accumulation of the contents within the duplicated bowel might have caused sepsis and enabled identification of the duplicated bowel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 8 ] suggested that attention should be paid to intestinal duplication in the abdominal cavity when mediastinal enterogenous cysts are noted, and vice versa . Khanna et al [ 9 ] also proposed that when a case of intestinal duplication is diagnosed, attention should be paid to whether there are concurrent duplications of other parts. Nazem et al [ 10 ] mentioned that there could be concurrent esophageal duplication cysts and small intestine duplication.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative prognosis is generally good, with few postoperative complications and a low recurrence rate. Khanna et al [ 9 ] reported that a neonate with total midgut duplication underwent staged surgery due to a poor general condition and long tubular duplication. The proximal cyst was excised in stage I. Postoperative reexamination revealed the presence of an enterogenous cyst in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%